2019
DOI: 10.3390/app9050881
|View full text |Cite
|
Sign up to set email alerts
|

Adamantane-Modified Graphene Oxide for Cyanate Ester Resin Composites with Improved Properties

Abstract: The conjugation of graphene and polymers has attracted great attention for the fabrication of functional hybrid nanomaterials. Here, we demonstrate the modification of graphene oxide (GO) with adamantane (AMT) through the diimide-activated amidation reaction. The modification of GO with AMT improves the dispersion and decreases the interfacial polarization of GO, causing a lower dielectric constant for the fabricated GO/AMT hybrid materials. The structures of GO/AMT were studied by Fourier transform infrared s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…Finally, we observed that the concentration of macromeres significantly enhanced the hydrogel toughness ( p < 0.05). It could be demonstrated that enhanced physical cross-linking of hydrogels led to considerably improved mechanical toughness [ 28 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we observed that the concentration of macromeres significantly enhanced the hydrogel toughness ( p < 0.05). It could be demonstrated that enhanced physical cross-linking of hydrogels led to considerably improved mechanical toughness [ 28 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…In that order, ester groups of Ad and GO at 1710 cm −1 and 1285 cm −1 were identified with the C=O and C-O bonds. The peaks at 3420, 1540, 1285, and 1140 cm −1 were also identified as GO distinctive peaks [ 30 , 34 ]. Three peaks on the CD were also found at 3405, 2920, and 1250 cm −1 , respectively, corresponding to the catechol, C-H, and C-O stretching of ether.…”
Section: Resultsmentioning
confidence: 99%
“…However, how PreEP with an uncured epoxy group reacts with CE still warrants discussion. As shown in Figure 2 (Table S1), the CE and EP/CE systems have only one curing exothermic peak in the reaction process, [15,42] while the PreEP/CE system has two peaks. Both exothermic peaks of PreEP/CE move to low temperatures when the PEA content increases.…”
Section: Curing Mechanism Of Preep/cementioning
confidence: 99%
“…Most methods of toughening polycyanate ester entail adding inorganic materials (aligned carbon nanotube bundles [ACNTB], [12] polyhedral oligosilsesquioxane [POSS)], [3,13,14] and graphene oxide [15] ) or polymers, [2,10,16,17] to the cyanate resin. Blending with inorganic materials can diminish the mechanical properties of the polycyanate ester [11][12][13] because of dispersion problems due to the presence of inorganic material in the resin matrix.…”
Section: Introductionmentioning
confidence: 99%
“…1 7 It is usually used as a resin matrix for advanced composites, adhesives and coatings used in the electronics, aerospace and military industries. 8 10 To meet the process requirements of these practical applications, it is necessary for bisphenol-A dicyanate ester to have good processability, including film-forming properties, melting fluidity and a wide processing window. However, the bisphenol-A dicyanate ester monomer (BADCy) has a symmetrical structure and is a powdery crystal at room temperature, which can not be used directly in the actual process, and is usually transformed into a prepolymer via thermal prepolymerization to improve its processability and controllability of use.…”
Section: Introductionmentioning
confidence: 99%